Efficacy and Safety of Radiofrequency Ablation for Breast Cancer Smaller Than 2 cm: A Systematic Review and Meta-Analysis - Xia, Lin-Yu; Hu, Qing-Lin; Xu, Wei-Yun (Frontiers in Oncology, 2021)
Background: To evaluate the efficacy and safety of radiofrequency ablation (RFA) of breast cancer smaller than 2 cm. Methods: A systematic search was conducted in the PubMed and EMBASE databases to identify published studies investigating the efficacy and safety of RFA for breast cancer smaller than 2 cm. The main outcomes were technical success rate of the ablation, complete ablation rate, complications and local recurrence. Secondary considerations were mode of anesthesia, pain tolerance, mean ablation time and surgical excision after ablation. Results: Seventeen studies involving 399 patients and 401 lesions met the inclusion criteria. Nearly 99%(95%CI=0.98-1.00) of lesions achieved good technical success rate.Notably, 83.88% of the patients received RFA under general anesthesia (333/397) whereas 15.87% received RFA under local anesthesia (63/397). Of the 63, 98.41% tolerated the pain associated with the procedure. Majority of patients (65.74%, 261/397) underwent surgical excision of the tumor after ablation whereas in a few patients (34.26%, 136/397), the tumor tissue was retained in the breast after ablation.Complete ablation was achieved in 96% of patients for a mean time of 15.8 minutes (95%CI=0.93-0.99). Overall, only 2% (95%CI=0.01-0.04) of the individuals developed complications. Skin burns (2.02%, 8/397) were the most common complications. There was no local recurrence after a median follow-up of 27.29 months, whether or not they underwent surgical resection following RFA. Conclusion: The results show that RFA for breast cancer smaller than 2 cm is safe and effective. However, prospective studies are needed to validate this conclusion.